Open access books: an international collaboration to explore the practical implications for librarians of increasing access to scholarly research outputs - Zhou, Elsie; Errelin, Leon; Oakley, Sam; Smyth, Neil (2018)
Open access advocacy and partnership is an established role for libraries across the world: books continue to be a challenge. Books and book chapters remain a vital output for many research areas. Open access policies have focused primarily on journal articles and serial publications, potentially creating an imbalance in the research literature freely available, and possibly having a negative impact on book publications in terms of readership and citations. Publisher permissions for journal articles can usually be accessed from Sherpa RoMEO, but book contracts continue to be a mostly hidden agreement between publisher and researcher, inaccessible to librarians who are supporting and driving the open access agenda within an institution. What are the current challenges for librarians in making academics books openly available? To what extent will this limit the mediating role of librarians in scholarly communication? Is this role sustainable? A global perspective is provided with a comparison of distinctive experiences at two leading international universities: Swansea University; and the University of Nottingham Ningbo China. Swansea University is seeking to create more open access book content in line with the United Kingdom’s Higher Education Funding Council for Education Research Excellence Framework Open Access policy. The University of Nottingham Ningbo China is seeking to maximize the dissemination and visibility of research to a global audience through open access.